Endoscopic-Assisted Transaxillary Approach for First Rib Resection in Thoracic Outlet Syndrome - Kozo Furushima, M.D; Tadanao Funakoshi, M.D; Hiroshi Kusano, M.D; Azusa Miyamoto, M.S; Toru Takahashi, M.D; Yukio Horiuchi, M.D; Yoshiyasu Itoh, M.D (Elsevier, 2021)
Purpose: To assess the feasibility, safety, and clinical outcomes of an endoscopic-assisted transaxillary approach of first rib resection for thoracic outlet syndrome (TOS) and to compare the differences in demographic and clinical data between satisfactory and unsatisfactory outcomes using this approach. Methods: We retrospectively identified patients who underwent endoscopic-assisted first rib partial resection. A transaxillary approach for the first rib resection and neurovascular decompression were undertaken under magnified visualization. Endoscopic classification of neurovascular bundle (NVB) patterns and interscalene distance (ISD) between anterior and middle scalene muscles were evaluated intraoperatively. We assessed the Roos and DASH scores. Results: We reviewed 131 cases of TOS (48 women and 83 men; mean age 26.2 years; range 12 to 57). Roos classification revealed 80.2% excellent or good results. DASH scores improved significantly from 40.7 ± 20.0 to 15.7 ± 19.6 (P < .001). The complication rate was low (5.3%), with 4 pneumothorax and 3 other complications. Intraoperative NVB classification revealed 30 cases of parallel type, in which the artery and nerve travel in parallel; 69 oblique types, and 30 vertical types, in which the nerve was completely behind the middle scalene muscle or abnormal band. The ISD was narrower (5.4 ± 3.6 mm) than in previous cadaveric studies. The ISD in the parallel patterns was wider than that in the vertical patterns. In the satisfactory group, we found a significantly larger number of men, younger patients, athletes, and patients with a lower preoperative DASH score. Conclusions: An endoscopic-assisted transaxillary approach for first rib resection in TOS provides an excellent magnified visualization, safely allowing sufficient decompression of the neurovascular bundle and satisfactory surgical outcomes. Younger male athletes with TOS may be better candidates for this procedure. Level of Evidence: IV, therapeutic case series.